2013
DOI: 10.1002/qj.2194
|View full text |Cite
|
Sign up to set email alerts
|

A new atmospheric dataset for forcing ice–ocean models: Evaluation of reforecasts using the Canadian global deterministic prediction system

Abstract: Despite the availability of several atmospheric reanalyses (e.g. ERA-Interim) there exists both considerable uncertainty in surface forcing fields for ice/ocean modelling and sensitivity to the choice of product used. Here we introduce a relatively high-resolution alternative forcing dataset for ice-ocean models derived from the Canadian Meteorological Centre's (CMC) global deterministic prediction system (GDPS). A set of daily 30 h reforecasts is produced using the GDPS 33 km resolution model providing hourly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 77 publications
0
87
0
Order By: Relevance
“…These include a coupled (atmosphere-ice-ocean) Gulf of Saint Lawrence system (officially operational since June 2011; Smith et al, 2012), the Global Ice-Ocean Prediction System (GIOPS, runs in real time since March 2014; Smith et al, 2015), a Great Lakes coupled system (still in development; Dupont et al, 2012), a regional ice-only prediction system (runs in real time since July 2013; Lemieux et al, 2015a) and a regional Arctic-North Atlantic ice-ocean system based on the CREG12 (Canadian REGional) configuration with a nominal horizontal resolution of 1/12 • . The last is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include a coupled (atmosphere-ice-ocean) Gulf of Saint Lawrence system (officially operational since June 2011; Smith et al, 2012), the Global Ice-Ocean Prediction System (GIOPS, runs in real time since March 2014; Smith et al, 2015), a Great Lakes coupled system (still in development; Dupont et al, 2012), a regional ice-only prediction system (runs in real time since July 2013; Lemieux et al, 2015a) and a regional Arctic-North Atlantic ice-ocean system based on the CREG12 (Canadian REGional) configuration with a nominal horizontal resolution of 1/12 • . The last is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term objective is to provide Canada with short-term ice-ocean predictions and hazard warnings in ice-infested regions. To evaluate the modelling component (as opposed to the analysis -or data-assimilation -component, which is not covered in this contribution), a series of hindcasts for the period 2003-2009 is carried out, forced at the surface by the Canadian GDPS reforecasts (Smith et al, 2014). These hindcasts test how the model represents upper ocean characteristics and ice cover.…”
mentioning
confidence: 99%
“…Open 25 boundary conditions (temperature, salinity and horizontal ocean velocities) are derived from the monthly GLORYS2v3 product as well. At the surface, the model is driven with high temporal (hourly) and spatial resolution (33 km) atmospheric forcing data provided by Canadian Meteorological Centre (CMC) Global Deterministic Prediction System (GDPS) ReForecasts (CGRF) dataset (Smith et al, 2014), including 10 m wind, 2 m air temperature and humidity, downwelling and longwave radiation flux, and total precipitation. Inter-annual monthly 1…”
Section: Numerical Model Setupmentioning
confidence: 99%
“…The CGRF product use the GEWEX correction (more details in Smith et al (2014)) to minimize the bias in the original output from the atmospheric model. However, it was found that this correction is not needed for years after 2011 (Paquin, 2017).…”
Section: May-10mentioning
confidence: 99%
“…Wind data was taken from the gridded reanalysis data of the Canadian Meteorological Centre (Smith et al, 2014). The location selected is on the Mackenzie Shelf, near the middle of the transect, located at 70.3125° N, 133.5937° W. Figure 6 shows the wind direction and magnitude averaged every six hours through August Sampling of the Mackenzie Shelf transect took place from August 22 nd to 24 th , indicated by the red lines in Fig.…”
Section: Wind Forcingmentioning
confidence: 99%